Cholesterol Microdomain Enhances the Biofilm Eradication of Antibiotic Liposomes (Adv. Healthcare Mater. 8/2022). Issue 8 (20th April 2022) - Xie, Jianjun; Meng, Zhiping; Han, Xingxing; Li, Sipan; Ma, Xinai; Chen, Xuanyu; Liang, Yinmei; Deng, Xiaomin; Xia, Kexin; Zhang, Yue; Zhu, Huaxu; Fu, Tingming
Abstract : Berberine Liposomes In article number 2101745 by Yue Zhang, Tingming Fu, and co‐workers, an engineered liposome containing cholesterol microdomain and berberine hydrochloride is developed for the eradication of Staphylococcus aureus biofilm. Liposomes with cholesterol microdomains significantly inhibit the growth of S. aureus, remove the bacterial biofilm, and lead to an almost complete recovery of rats with pulmonary infection. In addition, liposomes fuse better with bacterial cell membranes and have a stronger affinity for bacterial virulence factors, indicating that the tailored liposomes can combat bacterial biofilms and reduce tissue damage caused by toxins during bacterial eradication.